INTEGRASI KEPEMIMPINAN PEMBELAJARAN, BERPIKIR EVALUATIF, DAN TRANSFORMASI PENDIDIKAN DI ERA MODERN - Miskanik (Institut Ummul Quro Al-Islami Bogor, 2025)
This study examines the relationship between instructional leadership, evaluative thinking, and learning transformation as part of efforts to enhance the quality and relevance of education in the modern era. The research is grounded in the persistent tendency of many educational institutions to adopt administrative-centered leadership models that place limited emphasis on learning and innovation. The purpose of this study is to explain the interconnection among these three concepts and their application within both general education and Islamic education. The study employs a literature-based method through conceptual and comparative analysis of relevant academic sources. This analysis involves reviewing theories of instructional leadership, principles of evaluative thinking, and models of learning transformation to understand their functional relationships. Findings indicate that instructional leadership plays a central role in fostering an evaluative culture that supports evidence-based decision-making. Evaluative thinking strengthens the capacity of educators and leaders to assess the effectiveness of learning processes, while learning transformation is realized through digital innovation, collaborative learning, and flexible curriculum design. The synergy among these elements produces an educational system that is creative, adaptive, and globally competitive. In the context of Islamic education, the integration of faith, knowledge, and ethics provides spiritual and moral reinforcement that complements the transformation process